Translation and Genettean Hypertextuality: Catherine Magdalen Evelyn, Catherine of Bologna, and English Franciscan Textual Production, 1618–40 - Goodrich, Jaime (Renaissance and Reformation / Renaissance et Réforme, 2020)
Drawing on the ideas of Gérard Genette, this article argues for the value of reading translations as “hypertexts,” or as works grafted onto earlier texts (“hypotexts”), on the basis of the intriguing case study of The Admirable Life of the Holy Virgin S. Catharine of Bologna (1621), translated by Catherine Magdalen Evelyn of the Gravelines Poor Clares. Little-known today despite Evelyn’s importance as the most prolific female translator of the early Stuart period, this publication sublimates the voice of the translator through its laconic paratextual materials and its misattribution of Evelyn’s work to another nun. In spite of this carefully engineered authorial opacity, the stakes of Evelyn’s translation become clearer when it is read as part of a hypertextual system of Franciscan writings published in English, French, Italian, and Portuguese over the course of the sixteenth and seventeenth centuries. An analysis of how her text is grafted onto this series of hypotexts through bibliography, intertextuality, and translation results in a detailed, albeit speculative, account of Evelyn’s motivations for reading, translating, and publishing The Admirable Life. This seemingly modest publication is thus revealed as a rich hypertext that participated in a wider European project to chronicle the history of the Franciscan order. A concluding discussion of hypertextuality in early modern England briefly gestures more broadly toward the relevance of this method for studies of Renaissance literature.